Evaluation of echocardiographic findings of fabry patients: A single center experience (Annals of Medical Research, 2021)
Aim: Fabry disease is a lysosomal storage disease caused by α-galactosidase A enzyme deficiency due to mutation in the GLA gene with X-linked transition. Fabry disease may present with skin, eye, kidney, cardiac and neurological system involvement. Cardiovascular findings are important in terms of mortality due to differences in clinical presentation and difficulties in diagnosis. Cardiac involvement is the most common cause of mortality, therefore echocardiographic evaluation is important at baseline. Echocardiographic examination is a noninvasive and effective diagnostic method for the evaluation of cardiac involvement during both diagnosis and follow-up.Material and Methods: Echocardiographic findings of 18 patients who were followed up in the outpatient clinic for Fabry disease between August 2018 and December 2019 were retrospectively evaluated. All patients were evaluated for cardiac involvement by 2-dimensional echocardiography.Results: Between August 2018 and December 2019, there were 18 Fabry patients who were followed up in our hospital. In our study, 13 patients were female and 5 were male. The mean age was 42.2 ± 13.5 years. 12 patients with enzyme replacement therapy had different system involvement; Seven had cardiac involvement by echocardiography. The cardiac involvement rate of our symptomatic patients receiving treatment was 58.3% (7/12). Seven patients with cardiac involvement; Six (85.7%) had non-obstructive hypertrophic cardiomyopathy and stage 1 diastolic dysfunction in the left ventricle.Conclusion: In Fabry disease, cardiovascular findings are the most important cause of mortality and early diagnosis is important. The most common echocardiographic findings in our patient group were non-obstructive hypertrophic cardiomyopathy (85.7%) and left ventricular diastolic dysfunction. In the presence of unexplained non-obstructive hypertrophic cardiomyopathy, Fabry disease should be considered in the differential diagnosis. Fabry disease have multisystemic involvement, it requires absolute multidisciplinary approach in the diagnosis and follow-up of patients.